2003
DOI: 10.1210/en.2002-0088
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of Bovine Prostaglandin E2 Receptors EP2 and EP4: Expression and Regulation in Endometrium and Myometrium during the Estrous Cycle and Early Pregnancy

Abstract: Prostaglandins (PGs) play important functions in the reproductive system, and PGE(2) appears necessary for recognition of pregnancy. We have found that PGE(2) is able to increase cAMP generation in the bovine endometrium. There are two PGE(2) receptors (EP), EP2 and EP4, that are coupled to adenylate cyclase to generate cAMP, but these receptors have not been studied in the bovine. We have cloned and characterized bovine EP2 and EP4 receptors and studied their expression in the uterus. The amino acid sequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
2
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 55 publications
6
66
2
2
Order By: Relevance
“…The apparent mobilities for the EP2 and EP3 receptors (ϳ68 kDa and ϳ62 kDa, respectively) were different from the theoretical molecular masses predicted from the primary amino acid sequences (40 kDa and 40 -45 kDa, respectively) (22,54). This discrepancy between predicted and apparent molecular masses by SDS-PAGE has been reported previously with membrane receptors, including rat, bovine, and human EP receptors (55)(56)(57), and may result from receptor oligomerization (58) or posttranslational modifications such as glycosylation and/or phosphorylation (55,56). In agreement with our results, apparent mobilities of 68 and 62 kDa have also been reported for the human EP2 and EP3 receptors (55).…”
Section: Discussioncontrasting
confidence: 63%
“…The apparent mobilities for the EP2 and EP3 receptors (ϳ68 kDa and ϳ62 kDa, respectively) were different from the theoretical molecular masses predicted from the primary amino acid sequences (40 kDa and 40 -45 kDa, respectively) (22,54). This discrepancy between predicted and apparent molecular masses by SDS-PAGE has been reported previously with membrane receptors, including rat, bovine, and human EP receptors (55)(56)(57), and may result from receptor oligomerization (58) or posttranslational modifications such as glycosylation and/or phosphorylation (55,56). In agreement with our results, apparent mobilities of 68 and 62 kDa have also been reported for the human EP2 and EP3 receptors (55).…”
Section: Discussioncontrasting
confidence: 63%
“…Moderate expression of EP4 was demonstrated in the human , bovine (Arosh et al, 2003), and chicken (Kwok et al, 2008) testis, although no EP4 expression was detectable in the mouse or rat (Sando et al, 1994) testis.…”
Section: +mentioning
confidence: 94%
“…In female reproductive organs such as the ovary and uterus, hormonal exposure induces expression of the EP subtypes in a cell type-specific manner. EP4 is expressed in the mouse ovary (Segi et al, 2003) and in the human (Milne et al, 2001;Astle et al, 2005), baboon , mouse Yang et al, 1997), rat (Blesson et al, 2012), and guinea pig (Terry et al, 2008) uterus, although Arosh et al (2003Arosh et al ( , 2004 reported that EP4 mRNA was undetectable in the bovine uterus.…”
Section: +mentioning
confidence: 99%
“…Gene expression is given in italics and protein abundance is given in normal font. Data compiled from references [20,27,34,35,49,64,65,67,[74][75][76][77]. FORDE and LONERGAN 192 in both beef and dairy cattle have identified a correlation between concentrations of progesterone up to Day 7 following insemination and subsequent pregnancy rates [44,45].…”
Section: Cycle Related Changesmentioning
confidence: 99%
“…those that encoded for growth factors/ cytokines or those involved in the progression of the estrous cycle. The expression of insulin-like growth factor 2; IGFII, insulin-like growth factor binding protein 2, 36 kDa; IGFBP2 [48], prostaglandin E receptor 2 (subtype EP2), 53 kDa; PTGER2 [49], vascular endothelial growth factor receptor 2; VEGFR2 [50] in the endometrium, increases during the elongation stage of conceptus development while the expression of ESR1 [51], matrix metallopeptidase 2 (gelatinase A, 72 kDa type IV collagenase; MMP2 [52], and VEGF [50] declines. Treatment with exogenous progesterone increased the expression of uterine serpins [53] as well as PGR, ESR1 and retinol binding protein 4, plasma; RBP4 [54].…”
Section: Cycle Related Changesmentioning
confidence: 99%